MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS SISWA DALAM MENGHADAPI ERA REVOLUSI 4.0 - Sari, Linda; Lestari, Zuliana (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Many people assume that learning languages is easy because they think we have used language every day. Learning languages is not only able to communicate with the language, but also to know and understand the meaning contained in the words or phrases spoken. In learning languages, especially English, most students experience difficulties in speaking skill. The difficulty is usually caused by difficulties in expressing ideas verbally, limited vocabulary, limited grammar ability so that it is difficult to speak with the correct rules, limited ability to pronounce words (pronunciation) correctly. These result inthe students’ difficulties to pronounce the words correctly and lack of courage to speak because they are afraid of making mistakes. There are several effective ways to improve students’ speaking skill, namely increasing vocabulary, reading aloud, recognizing simple English grammar, reading English writing, practising English conversation, listening to English songs, watching Englishmovies, andbeing fond of English. This paper also discusses the method of teaching using role play and media of picture strip stories to improve students' English speaking skill.